Outcome of surgically treated Lisfranc injury: A review of 34 cases - Miswan, Mohd Fairudz Mohd; Singh, Vivek Ajit; Yasin, Nor Faissal (Kare Yayincilik ve Iletisim Hizmetleri, 2011)
BACKGROUND We reviewed cases with Lisfranc injuries who presented to our center in order to study the adequacy of the treatment method and their final functional outcome. METHODS This is a retrospective review of 34 cases diagnosed with Lisfranc injuries treated at our center from 2000 to 2006. This review is aimed to determine the demography and functional outcome of all patients with Lisfranc injury treated during this period. RESULTS The injury was classified based on the "Hardcastle and Associates Classification". In our review, we found that the commonest Lisfranc injury was type B2 (41). These injuries are mostly fixed with K-wires (76.5). All patients assessed with Bristol Foot Score (BFS) had a good score in all categories, with a total score ranging from 16 to 25. CONCLUSION We concluded that all Lisfranc injuries, whether treated with closed or open fixation methods, demonstrated a good long-term functional outcome.